The tongue flap for large palatal fistulas, a success or a failure? Our 15-year experience - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2020)
Large palatal fistulas after cleft palate surgery are difficult to treat using local mucoperiosteal flaps alone, particularly if multiple attempts to close the fistulas have resulted in tissue scarring. In this study, we present our 15-year surgical experience with tongue flaps for large palatal fistulas. A total of 34 patients who underwent tongue flap surgery at our institution between January 2000 and January 2015 were retrospectively analyzed. An anteriorly-based dorsal tongue flap was used for the treatment of anteriorly localized large palatal fistulas in all patients. Data including demographic characteristics of the patients, previous surgeries, localization of the fistula, time between the first and second surgery, and complications were recorded. Factors affecting the surgical success were evaluated. Of the patients, 21 were males and 13 were females with a mean age of 11.7 +/- 6.9 (range: 4 to 29) years. Detachment of the tongue flap was observed in nine patients after surgery. Seven of the patients with detachment were male aged <= 6 years (p < 0.05). Resuturing the flap back to the defect did not significantly affect the results. Our study results suggest that proper patient selection and attentive and rigorous surgical technique have a critical importance in the tongue flap repair and tongue flap is not recommended for patients who are under seven years of age.
Keywords: Palatal fistula; tongue flap; cleft palate; cleft lip-palate; CLOSURE; REPAIR; MANAGEMENT; RESONANCE